MOBILE SEAMLESS LEARNING FOR FUTURE LEARNING MODELS - Abdul Haris Indrakusuma (STKIP PGRI TULUNGAGUNG, 2023)
The learning process that emerges scientifically is one of the current learning emphases. The development of mobile technology such as smartphones supports learning that occurs outside of context, that is, it can occur at any time and anywhere without being bound by time and space. This has the opportunity to create learning that arises naturally. Students can be accommodated to study anytime and anywhere according to the students wishes or learning mood. Therefore, appropriate concepts and designs are needed to provide an effective learning environment. Mobile seamless learning is a learning model that contains the concept of continuity and continuity in the learning process that occurs without boundaries of space and time. This article describes the general concept in developing Mobile Seamless Learning-based learning